2015
DOI: 10.1002/cphc.201500396
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resonance Stabilization on the Intramolecular Hydrogen‐Atom Shift Reactions of Hydrocarbon Radicals

Abstract: A series of intramolecular H-atom shift reactions of both alkenyl and allylic radicals were investigated by using CBS-QB3 electronic structure calculations. In the first set of reactions, an alkyl radical site was converted into an allylic radical site. In the second set, an allylic radical was converted into another allylic radical. The results are discussed in the context of a Benson-type model to examine the impact of the transition-state partial resonance stabilization on both the activation energies and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Thus, the CPO-3 radical is more reactive and in the absence of other interfering reactions will primarily decompose by elimination of carbon monoxide to yield the 3-buten-1-yl radical, H 2 CCH–CH 2 ĊH 2 . Subsequent reactions of this radical, such as a 1,2-hydrogen shift to form an allylic system, , have been thoroughly explored in recent times by Dean et al and Miyoshi …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the CPO-3 radical is more reactive and in the absence of other interfering reactions will primarily decompose by elimination of carbon monoxide to yield the 3-buten-1-yl radical, H 2 CCH–CH 2 ĊH 2 . Subsequent reactions of this radical, such as a 1,2-hydrogen shift to form an allylic system, , have been thoroughly explored in recent times by Dean et al and Miyoshi …”
Section: Resultsmentioning
confidence: 99%
“…3 , have been thoroughly explored in recent times by Dean et al 39 and Miyoshi. 40 We note that species corresponding to C 4 H 7 + were detected by mass spectrometry in the very recent flow tube experiments 10 of Cl • + CPO at 550−650 K both in the presence and in the absence of O 2 , which is supporting evidence of the essential correctness of the ring-opening and β-scission routes calculated here.…”
mentioning
confidence: 99%
“…H-atom migration due to radicals on alkyl chains has been studied computationally and experimentally in hydrocarbon combustion and pyrolysis and in polymer production and degradation processes. Here, the formation of additional short branches in low-density polyethylene (PE) attributed to H-atom migration is the best known example, , but H-atom migration has also been proposed during oxidation of PP . The general scheme of this class of reactions, also known under the name “mid-chain radical migration,” , is shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Similar schemes were also applied by Ghent, , Kang , and other groups, which used ab initio group contribution method for activation energies for radical additions. Alternatively, a set of rate rules based on the high-level calculations of the model systems, which can be applied to a range of analogous reactions, was proposed by Dean and co-workers. Systematic, based on high level CBS-Q, G2, and G4 composite computational methods, and study of H migrations in hydrocarbons, including cyclic species, were reported by Davis et al …”
Section: Introductionmentioning
confidence: 99%